Radiation recall dermatitis induced by COVID-19 vaccination in breast cancer patients treated with postoperative radiation therapy. (October 2022) - Vinante, Lorenzo; Caroli, Angela; Revelant, Alberto; Bertini, Federica; Giroldi, Anna; Marson, Marta; Franchin, Giovanni; Muraro, Elena; Brisotto, Giulia; Steffan, Agostino; Baboci, Lorena
Abstract: Background: and purpose: Radiation recall dermatitis is an adverse event predominantly due to systemic therapy administration after a previous radiation therapy course. Few case reports describe radiation recall dermatitis in breast cancer patients treated with postoperative radiation therapy following COVID-19 vaccination. In this study we investigated the incidence and severity of radiation recall dermatitis after COVID-19 vaccination in irradiated breast cancer patients. Methods: Patients that received at least one COVID-19 vaccination dose during the year after the end of postoperative breast radiation therapy were included in this observational monocentric study. Local symptoms occurring inside the radiation field after vaccination were patient-reported and scored according to the PRO-CTCAE questionnaire. Descriptive data of radiation recall dermatitis incidence and severity, and potential risk factors were evaluated. Results: A cohort of 361 patients with 756 administered COVID-19 vaccinations was analyzed. Breast symptoms were reported by 7.5% of patients, while radiation recall dermatitis was considered for 5.5%. The incidence of radiation recall dermatitis per single dose of vaccine was 2.6%, with a higher risk for the first dose compared to the second/third (4.4% vs 1%, p = 0.003), especially when administered within the first month after the end of irradiation (12.5% vs 2.2%, p = 0.0004). Local symptoms were generally self-limited and a few cases required anti-inflammatory drugs. Conclusions: Radiation recall dermatitis is an uncommon but not rare phenomenon in breast cancer patients that received COVID-19 vaccination within one year after breast irradiation. However, symptoms severity were generally low/mild and reversible. These findings can be useful for patient counseling. Highlights: First study that reported the incidence of radiation recall dermatitis after COVID-19 vaccination in breast cancer patients. Radiation recall dermatitis after COVID-19 vaccination was not a rare event in breast cancer patients. Symptom severity of radiation recall dermatitis after COVID-19 vaccination was low/moderate and self-limiting.